Implementation of Information System at SD Laboratorium UNG - Moligai, Nurfahmi; Djafri, Novianty (CV. Media Inti Teknologi, 2024)
This research aims to find out the implementation of the human resource information system at SD Laboratorium UNG. The purpose of the information system is to help organize all functional areas of human resource management efficiently. SD Laboratorium UNG is a school that has been accredited as superior. This mini-research was conducted using a qualitative approach and data collection techniques in the form of observation, interviews, and documentation, and data presentation was carried out using a descriptive approach, in the form of words, writing, or oral from the subjects observed, namely the principal and teachers. Based on the mini research that has been carried out, the results show that the implementation of the Human Resource Management System at SD Laboratorium UNG has been carried out, but it has not been carried out optimally, but the school has been able to utilize the development of information and communication technology for the progress of the school towards a better direction. The applications used at SD Laboratorium UNG are Facebook, YouTube, Instagram, Email, Zoom, Google Drive, WhatsApp, Ms.Word, Ms.Exel, and JunioSmart.